2009
DOI: 10.1111/j.1551-2916.2009.03030.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Displacement Rates on the Densification of Nanostructured Zirconia by Current Activation

Abstract: Nanostructured yttria‐stabilized zirconia powder (fully and partially stabilized) was densified using simultaneous applied current and pressure using varying displacement control rates for pressure application. The varying displacement rates were found to significantly affect densification rates as well as the final density of the products at all temperatures in the study. The densification rates were significantly higher than those previously reported without current application. In addition the effective den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…An activation energy of 620 kJ/mol for HP and 630 kJ/mol for FAST was also determined from the macroscopic behavior. The lower values for the activation energy found by Xu et al 49 . on SPS specimens were measured immediately after heating at a rate of 200 K/min.…”
Section: Discussionsupporting
confidence: 70%
“…An activation energy of 620 kJ/mol for HP and 630 kJ/mol for FAST was also determined from the macroscopic behavior. The lower values for the activation energy found by Xu et al 49 . on SPS specimens were measured immediately after heating at a rate of 200 K/min.…”
Section: Discussionsupporting
confidence: 70%
“…Contact resistance has been identified previously as a reason for the temperature differences between the surface of the graphite die and the center of the sample 110,111 . Another aspect of the pressure, the rate at which it is applied, was investigated by Xu et al 112 in the densification of YSZ. They found that the displacement rates affected the densification rates and the final density of the samples significantly.…”
Section: Pecs Parameters and Their Effect On Processingmentioning
confidence: 99%
“… Time evolution of the relative density of eight YSZ samples processed using varying displacement control rates at 1200°C 112 …”
Section: Pecs Parameters and Their Effect On Processingmentioning
confidence: 99%
“…It should be noted that the material may densify by plastic yielding if the applied stress is high enough. However, it does not seem likely that this would occur under present stress value as discussed by the previous work [10]. The possible influence of plastic deformation of particles/grains on packing was neglected in the present work.…”
Section: Discussionmentioning
confidence: 82%
“…Neither the underlying densification mechanism(s) nor relationship of individual sintering stages has been well distinguished, yet. Using four classic pressure-assisted models, Xu et al [10] reported that the effective activation energies for early densification in SPS were considerably lower than that expected for any diffusion-related process. In those regards, possible mechanism(s) besides the classic atomic diffusion-related processes was suspected to be involved in SPS process.…”
Section: Introductionmentioning
confidence: 98%